2016
DOI: 10.3846/13923730.2016.1176597
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Pile Stiffness on the Ground Slab Behaviour

Abstract: Abstract. Just as other structural elements, ground slabs are an important unit of a building. It is especially true in the case of buildings, such as logistic centres, for which the primary purpose is storage of various goods. In this kind of buildings, floor slabs usually have high loads. For buildings where truck lifts are used, there are special requirements for flatness tolerance across and along the driving track of truck lifts. Therefore, the floor settlement differences in selected distances are limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 15 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…A realistic representation of the load sharing between pile shaft and pile base is critical in the analysis of geotechnical structures, including deep foundation elements. For example, Zhou et al [69] have reported that the development of differential settlements, developing between the pile and surrounding soil, is more pronounced for end-bearing piles, in comparison with floating piles. In addition, the load-carrying mechanism influences the development of skin tractions along the pile length, hence, this is of paramount importance in the analysis of composite foundations such as piled rafts [70].…”
Section: Influence Of Mesh Size On Pile Load Transfer Mechanismmentioning
confidence: 99%
“…A realistic representation of the load sharing between pile shaft and pile base is critical in the analysis of geotechnical structures, including deep foundation elements. For example, Zhou et al [69] have reported that the development of differential settlements, developing between the pile and surrounding soil, is more pronounced for end-bearing piles, in comparison with floating piles. In addition, the load-carrying mechanism influences the development of skin tractions along the pile length, hence, this is of paramount importance in the analysis of composite foundations such as piled rafts [70].…”
Section: Influence Of Mesh Size On Pile Load Transfer Mechanismmentioning
confidence: 99%
“…Perhaps the most reliable type of piles is a jacked pile. The piles are Medzvieckas, J.;Sližytė, D. 2016. Jacked pile interaction with strengthened foundation 277 pushed into the ground.…”
Section: Underpinning Constructionmentioning
confidence: 99%
“…However, when the load is close to the limit, the stiffness of the piles should be much lower 10 000 and 40 000 kN/m. Urbonas et al (2016) carried out analyses of piles stiffness based on the static test. Calculated piles stiffness values when settlements varied from 0.97 to 4.89% of the piles diameter were obtained respectively from 125 000 to 38 000 kN/m.…”
Section: Fig 5 Foundation Displacementmentioning
confidence: 99%
“…As an alternative to the weak soils' replacement, chemical stabilization or soil reinforcement using rigid inclusions (Ardah et al, 2017) can be used. As an additional option for extremely weak soils, the floor slab can be supported on piles (Urbonas et al, 2016). In this case, the settlements of the slab could be greatly reduced and the differences of relatively small settlements would not exceed limit values.…”
Section: Introductionmentioning
confidence: 99%